The effects of physical exercise on the time management of college students: a chain mediation effect test - Cao, Yue; Jiang, Yong (Frontiers in Psychology, 2025)
In an era of increasing academic pressures and digital distractions, time management has become an important competency for college students, with significant implications for their academic performance, psychological wellbeing, and lifelong success. Drawing on the frameworks of social cognitive theory and neurobehavioral science, the present study aimed to investigate the effects of physical activity on college students’ time management ability and its psychotransmission mechanisms, with a particular focus on the interlocking mediating roles of sensation-seeking and self-efficacy. A questionnaire was administered to 714 Chinese university students (mean age 20.3 ± 1.8 years), and the data were analyzed using structural equation modeling (SEM, a statistical method for analyzing complex relationships among variables) and the Bootstrap method (a re-sampling technique for assessing statistical significance). The results indicated that (1) physical activity had a significant and strong positive predictive effect on college students’ time management ability (β = 0.416, p < 0.001); (2) sensation seeking (effect size = 0.067) and self-efficacy (effect size = 0.065) each played a moderately independent mediator role; and (3) the chained mediation paths formed by the two (effect size = 0. 017) further explained 3.31% of the variance, suggesting that physical activity indirectly optimized time management through the sequential path of “stimulus-driven behavioral choice → reinforcing efficacy beliefs → optimizing goal execution.” In addition, it was found that the degree of exercise structuring (e.g., a team training program) significantly enhanced the cascade effect (β = 0.15, p < 0.05), whereas high-intensity interval training (HIIT) may weaken the transfer efficiency due to short-term cognitive load. The findings contribute to the construction of an integrated “behavioral-psychological-behavioral” model that reveals the complex mechanisms by which physical activity affects time management, and practically suggests that colleges and universities should design a collaborative program of “structured physical education curriculum + cognitive training” to systematically improve students’ time management ability and academic efficacy.